Gestión de la supervisión y eficiencia operativa en la Municipalidad de Contamana, 2024 - Paredes Horna, Antony (2025)
The purpose of this study was to establish the relationship between supervision management and operational efficiency in the Municipality of Contamana, 2024. To achieve this, a basic study was carried out with a descriptive-correlational approach and non-experimental design. To this end, a research was carried out with a descriptive-correlational approach and non experimental design. The sample was composed of 85 collaborators. The findings indicated that supervision was rated as fair (27%). This perception was explained by the fact that, on certain occasions, the training provided by the committee responsible for supervision was not constant. Regarding operational efficiency, it also obtained a rating of fair (27%), due to the fact that workers sometimes met the assigned objectives, made adequate use of institutional resources and delivered tasks according to the established standards. Finally, the statistical test reported a correlation coefficient ρ = 0.720 and a bilateral significance of 0.000, which demonstrated a positive and highly significant association between supervisory management and operational efficiency in the analyzed institution.